2014
DOI: 10.1016/j.pain.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Is all pain is treated equally? A multicenter evaluation of acute pain care by age

Abstract: Pain is highly prevalent in healthcare settings, however disparities continue to exist in pain care treatment. Few studies have investigated if differences exist based on patient related characteristics associated with aging. The objective of this study was to determine if there are differences in acute pain care for older versus younger patients. This was a multicenter, retrospective, cross-sectional observation study of 5 emergency departments across the US evaluating the 2 most commonly presenting pain cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…This might be due to poor quality of life and increased probability of physical disability in older people [28]. Although almost all findings in the clinical literature are consistently pointed towards an increase in clinical pain with age [2,24,29,30], the effects of aging on pain perception remain unclear [16].…”
Section: Age Differences In Clinical Painmentioning
confidence: 99%
“…This might be due to poor quality of life and increased probability of physical disability in older people [28]. Although almost all findings in the clinical literature are consistently pointed towards an increase in clinical pain with age [2,24,29,30], the effects of aging on pain perception remain unclear [16].…”
Section: Age Differences In Clinical Painmentioning
confidence: 99%
“…This was a retrospective review of data from a multicenter cohort of 1,782 patients collected by Hwang et al for a study on age-related disparities in emergency department pain care [7]. The original study by Hwang et al found no age-related disparities in differences in fracture pain care.…”
Section: Design and Settingmentioning
confidence: 99%
“…This study received institutional board approval with a waiver of informed consent at all five sites. Further details about the sample assembly can be found in the original paper by Hwang et al [7].…”
Section: Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations